Modelling and Control Analysis of Dividing Wall Distillation Columns (DWC) (University of Khartoum Engineering Journal, 2022)
This work aims to study the behavior of fluid mixtures in the dividing wall column, particularly from acontrollability point of view. It covers the aspects of design, modeling, and control. A ternary mixture of benzene,toluene, and o-xylene (BTX) is selected as a case study. A controllability analysis for determining and screeningthe candidate control combinations of the manipulated variables is carried out with the aid of a linearized modelusing the concept of relative gain array (RGA). The manipulated variables are the reflux (L), the distillate (D), theside stream (S), the bottom (B) and the boilup (V). Based on RGA criterion, two of the candidate combinations areselected to control the column due to the low interaction between control loops. These combinations are DV/SLBand LB/DVS. In each combination the manipulated variables are used to control the top level, the bottom level, thetop composition, the middle composition and the bottom composition respectively. Finally the performance ofthese two combinations is examined and found to be successful in resisting the disturbances.